Extracellular vesicles containing oncogenic mutant β‐catenin activate Wnt signalling pathway in the recipient cells. Issue 1 (15th November 2019) - Kalra, Hina; Gangoda, Lahiru; Fonseka, Pamali; Chitti, Sai V.; Liem, Michael; Keerthikumar, Shivakumar; Samuel, Monisha; Boukouris, Stephanie; Al Saffar, Haidar; Collins, Christine; Adda, Christopher G.; Ang, Ching‐Seng; et al.
ABSTRACT: Mutations in β‐catenin, especially at the residues critical for its degradation, render it constitutively active. Here, we show that mutant β‐catenin can be transported via extracellular vesicles (EVs) and activate Wnt signalling pathway in the recipient cells. An integrative proteogenomic analysis identified the presence of mutated β‐catenin in EVs secreted by colorectal cancer (CRC) cells. Follow‐up experiments established that EVs released from LIM1215 CRC cells stimulated Wnt signalling pathway in the recipient cells with wild‐type β‐catenin. SILAC‐based quantitative proteomics analysis confirmed the transfer of mutant β‐catenin to the nucleus of the recipient cells. In vivo tracking of DiR‐labelled EVs in mouse implanted with RKO CRC cells revealed its bio‐distribution, confirmed the activation of Wnt signalling pathway in tumour cells and increased the tumour burden. Overall, for the first time, this study reveals that EVs can transfer mutant β‐catenin to the recipient cells and promote cancer progression.